Keterampilan Berbicara pada Pembelajaran Bahasa Indonesia Siswa Kelas I SDN Bhayangkari - Cipta, Nana Hendra; Rokmanah, Siti; Mulki, Siti Tria Malikal (FONDATIA, 2023)
The purpose of this preliminary study is to explain how the teacher's role in improving the speaking skills of grade I students of SDN Bhayangkari. This research method is descriptive research. The research techniques used in this research are qualitative and quantitative. The implementation time of this introduction was carried out on October 25, 2022 until completion. This introductory study involved grade I students of SDN Bhayangkari and one teacher or homeroom teacher. The results of the observation showed that students were able to carry out speaking skills very well. From the test results, twenty students received excellent scores. The improvement of students' speaking skills has five roles of a teacher, namely the teacher motivates students' skills, the teacher as a facilitator, provides opportunities for students to perform, learning methods, and learning media that are suitable for improving students' speaking skills.